Effect of Mixing Time to Homogeneity of Propellant Slurry - Luthfia H. Abdillah; Sugeng Winardi; Sumarno Sumarno; Tantular Nurtono (Institut Teknologi Sepuluh Nopember, 2018)
Propellant is a rocket fuel that can be solid or liquid. This research focused on composite solid propellant that was made from solid and liquid materials become a slurry. Homogeneity of the propellant slurry is important to investigate because it can affect specification and performance of the propellant. This research objective was to study effect of mixing time to homogeneity of propellant slurry that was processed by horizontal sigma blade mixer. Density data were used to assess the homogeneity and stated as degree of homogeneity. The result showed that the mixing time affect the density values and it was obtained the most homogeneous slurry was at total mixing time 135 minute